Teacher Strategies In Handling Children With Disorders Communication (Case Study at SLB Pulau Punjung Dharmasraya) - Sonia Yulia Friska; Asep Supena; Totok Bintoro (CV. Rayyan Dwi Bharata, 2024)
There aren't many studies that address ABK's speech delay, but research reports on similar topics can be found easily. Therefore, the author concentrates on explaining the teacher's way of dealing with children's speech delays. This study aims to find out how teachers and parents deal with children with speech delay disorders. This research was conducted using qualitative case study method. The results showed that some of the children's characteristics were unable to understand and respond to peers, parents, or adults around them; they were less likely to talk (quiet), unable to form simple sentences when asked something; they often used vague, rigid, or stammered language because they lacked vocabulary; and they usually used confused language when speaking. To encourage delays in children's speech, strategy treatment is carried out: 1) training children to speak correctly, slowly, and repeatedly; and 2) always pay attention to grammar when speaking.